Method for efficiently preparing polyphenyl ether
By optimizing the reaction conditions and catalysts during the preparation of polystyrene ether, the activated carbon carrier and copper nanoparticles are used to combine the reaction of the modifier to solve the problems of high temperature, complex catalytic and by -products in existing technologies. Efficient and environmentally friendly polystyrene preparation has improved product performance and application potential.
Patent Information
- Application Number
- CN202411560380.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyphenylene ether preparation methods have problems such as high temperature demand, complex catalyst systems, many by-products, equipment corrosion and environmental impact, and it is difficult to meet the high requirements of modern industry for the performance of polyphenylene ethers.
Use bisphenol A, potassium iodide and sodium hydroxide to react in the reactor, add copper powder catalysts and solvents, control the reaction temperature and time, use the use of active carbon carriers and copper nanoparticles, combine the modifier reaction, optimize the catalytic system and the post -latter Processing steps to improve product performance.
It significantly improves the synthesis efficiency and product quality of polyphenylene ether, reduces the generation of harmful solvents and by-products, and improves the mechanical properties, heat resistance and electrical properties of the product. It is suitable for electronic materials, automotive parts, medical equipment and other fields.
Smart Images

Figure CN119331241A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering plastic preparation, and more specifically to a method for efficiently preparing polyphenylene ether. Background Art
[0002] As an engineering plastic, polyphenylene ether (PPO) is widely used in many fields due to its excellent mechanical properties, high temperature resistance and electrical insulation properties, especially in electronic materials, automotive parts and medical devices. The main preparation methods of polyphenylene ether include oxidative coupling and core substitution. However, these traditional methods have some problems that restrict their efficiency and product performance.
[0003] Traditional oxidative coupling methods require high temperatures and usually use complex metal catalyst systems, which not only increases production costs but also may lead to catalyst instability and complex post-processing steps. In addition, this method may produce a large number of by-products, the presence of which will reduce the purity and performance of the product.
[0004] Although the core substitution method can be carried out at a lower temperature, it usually requires the use of strong bases and halogen compounds. The use of these reagents is not only highly corrosive to the equipment, but also has an impact on the environment that cannot be ignored. In addition, this method requires high purity of the raw materials, and the slightest carelessness may lead to unstable performance of the final product.
[0005] With the development of industry and technology, the demand for polyphenylene ether is also changing. Modern industry has put forward higher requirements on the performance of polyphenylene ether, including better mechanical properties, heat resistance and electrical properties, to adapt to more extreme working environments and more complex application scenarios. Therefore, the development of a new efficient and environmentally friendly method for preparing polyphenylene ether has become an important demand of the industry. Summary of the invention
[0006] 1. Technical problems to be solved
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for efficiently preparing polyphenylene ether. By fully reacting specific components in a reactor, the reaction steps are simple and efficient, and the polyphenylene ether can be prepared without complex processes. The present invention also introduces activated carbon carriers and copper nanoparticles in the catalyst preparation stage, and improves the performance of the final product by reacting with specific modifiers. In addition, the final polyphenylene ether product is suitable for electronic materials, automotive parts, medical devices and other fields, showing its wide application potential and technical value. The innovation of the present invention lies in the optimization of its catalytic system and the precise control of the performance of the finished product, which effectively improves the production efficiency and product quality of the polyphenylene ether.
[0008] 2. Technical solution
[0009] To solve the above problems, the present invention adopts the following technical solutions.
[0010] A method for efficiently preparing polyphenylene ether comprises the following steps:
[0011] S1, mixing bisphenol A, potassium iodide and sodium hydroxide in a reactor;
[0012] S2, adding a solvent to the reaction mixture and mixing it thoroughly, adding a catalyst to the mixture, and then heating the reaction;
[0013] S3. After the reaction is completed, the reaction mixture is cooled to room temperature, and a precipitant is added thereto to precipitate a polyphenylene ether product;
[0014] S4. The polyphenylene ether product is filtered, washed and dried to obtain a finished product.
[0015] As a further improvement of the present invention, in step S1, the molar ratio of bisphenol A to potassium iodide is 1:1.2 to 1:1.8, and the amount of sodium hydroxide used is 15%-25% of the weight of bisphenol A.
[0016] As a further improvement of the present invention, the solvent in step S2 is selected from at least one of xylene, dichloromethane and N,N-dimethylformamide, and the amount used is 2 to 5 times the weight of bisphenol A;
[0017] The catalyst is copper powder, and its usage is 0.1%-0.5% of the weight of bisphenol A.
[0018] As a further improvement of the present invention, the reaction temperature in step S2 is controlled between 130° C. and 160° C., and the reaction time is 20 to 60 minutes.
[0019] As a further improvement of the present invention, in step S3, the precipitant is selected from at least one of water, ethanol and acetic acid, and its addition amount is 30%-50% of the volume of the reaction mixture.
[0020] As a further improvement of the present invention, the step S4 modifies the finished product, and the modification treatment includes reacting with at least one modifier selected from maleic anhydride, vinyltriethoxysilane and methyl methacrylate.
[0021] As a further improvement of the present invention, the modification treatment comprises the following steps:
[0022] S41, mixing the finished product with a modifier in a solvent of toluene or xylene, wherein the amount of the modifier is 1%-10% of the weight of the finished product;
[0023] S42, heating the mixture to 80° C.-150° C. and maintaining the temperature for 5-12 hours to ensure that the modifier and the polyphenylene ether react fully, and the reaction is carried out under a nitrogen atmosphere;
[0024] S43. After the reaction is completed, the product is cooled and washed with a suitable solvent to remove unreacted modifier and by-products, and then dried.
[0025] As a further improvement of the present invention, the step S2 of loading the catalyst comprises the following steps:
[0026] S21, select commercially used activated carbon and calcine it at 400°C for 2 hours to remove surface impurities and improve purity, the amount of activated carbon used is 10% of the total reaction system mass;
[0027] S22, using copper sulfate as a copper source to prepare a 0.1 M solution, and using sodium borohydride (NaBH4) as a reducing agent to ensure complete reduction of copper ions to form copper nanoparticles;
[0028] S23, ultrasonically treating the mixture for 2 to 4 hours to ensure that the material is evenly dispersed;
[0029] S24, drying the mixture at 200° C. using a nitrogen atmosphere for 3-5 hours;
[0030] S25, calcining at 300°C to 500°C for 2 hours, maintained under an inert gas atmosphere.
[0031] As a further improvement of the present invention, in step S22, carbon nanotubes or graphene are added to the solution in an amount of 1%-5% of the amount of activated carbon.
[0032] As a further improvement of the present invention, the polyphenylene ether product is used for at least one application after filtering, washing and drying, and the application includes electronic materials, automobile parts or medical devices.
[0033] 3. Beneficial effects
[0034] (1) The present invention significantly improves the synthesis efficiency of polyphenylene ether by optimizing the reaction conditions and the use of catalysts. In particular, by using an improved copper-based catalyst, the temperature and time required for the reaction are reduced, and the conversion rate and selectivity of the reaction are improved.
[0035] (2) This method reduces the generation of harmful solvents and by-products and is more environmentally friendly than traditional methods. The solvents and precipitants used are easy to recycle and reuse, reducing waste emissions.
[0036] (3) The present invention involves loading treatment of the catalyst by controlling the reaction conditions and post-processing steps. The preferred activated carbon can assist the catalyst to be better dispersed in the reaction system. The advantages of activated carbon loading are its high specific surface area and porous structure, which makes activated carbon an excellent carrier material. It can provide more active sites, enhance the dispersibility of the catalyst, thereby improving the catalytic efficiency. The obtained polyphenylene ether product has better molecular weight distribution and purity, thereby showing more excellent mechanical properties and temperature resistance.
[0037] (4) The present invention adjusts factors such as the type and amount of the catalyst, the reaction temperature and time, especially the carbon nanotubes and graphene introduced in the post-treatment step, which have excellent thermal conductivity, not only promoting the conduction and distribution of temperature in the heated reaction system, so that the catalytic performance of the catalyst is stably improved, but also greatly improving the thermal stability of the polyphenylene ether product. The introduction of graphene sheets into the catalyst can also enhance the conductivity of the catalyst and promote the rapid transmission of electrons, thereby improving the reaction rate and efficiency, thereby accurately controlling the molecular structure and performance of the polyphenylene ether to meet the specific needs of different application fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a preparation method diagram of the present invention;
[0039] Figure 2 This is a performance characterization table of the polyphenylene ether products of Examples 1-7 of the present invention. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.
[0041] Embodiment 1:
[0042] Bisphenol A is mixed with potassium iodide and sodium hydroxide in a reactor, which can be a microwave reactor with a power of 500 watts. Xylene is added to the reaction mixture and mixed thoroughly. Copper powder is added to the mixture, and then heated for reaction. The reaction temperature is controlled at 130° C. and the reaction time is 20 minutes. After the reaction is completed, the reaction mixture is cooled to room temperature, and ethanol is added thereto to precipitate a polyphenylene ether product. The polyphenylene ether product is filtered, washed and dried to obtain a finished product, wherein the molar ratio of bisphenol A to potassium iodide is 1:1.2, the amount of sodium hydroxide is 15% of the weight of bisphenol A, the amount of xylene is 2 times the weight of bisphenol A, the amount of copper powder is 0.1% of the weight of bisphenol A, and the amount of ethanol is 30% of the volume of the reaction mixture.
[0043] Embodiment 2:
[0044] Bisphenol A is mixed with potassium iodide and sodium hydroxide in a reactor, which can be a microwave reactor with a power of 500 watts. Xylene is added to the reaction mixture and mixed thoroughly. Copper powder is added to the mixture, and then heated for reaction. The reaction temperature is controlled at 160° C. and the reaction time is 60 minutes. After the reaction is completed, the reaction mixture is cooled to room temperature, and ethanol is added thereto to precipitate a polyphenylene ether product. The polyphenylene ether product is filtered, washed and dried to obtain a finished product, wherein the molar ratio of bisphenol A to potassium iodide is 1:1.8, the amount of sodium hydroxide is 25% of the weight of bisphenol A, the amount of xylene is 5 times the weight of bisphenol A, the amount of copper powder is 0.5% of the weight of bisphenol A, and the amount of ethanol is 50% of the volume of the reaction mixture.
[0045] Embodiment 3:
[0046] On the basis of Example 2, commercially used activated carbon was selected and calcined at 400°C for 2 hours to remove surface impurities and improve purity. The amount of activated carbon was 10% of the total reaction system mass. Copper sulfate was used as the copper source to prepare a 0.1M solution. Sodium borohydride (NaBH4) was used as a reducing agent to ensure complete reduction of copper ions to form copper nanoparticles. The mixture was ultrasonically treated for 3 hours to ensure uniform dispersion of the material. The mixture was dried at 200°C for 4 hours in a nitrogen atmosphere and calcined at 400°C for 2 hours, maintained in an inert gas atmosphere. The obtained catalyst was used to replace the copper powder in Example 2, and the remaining steps remained consistent.
[0047] Embodiment 4:
[0048] On the basis of Example 3, graphene sheets were added to the solution in an amount of 5% of the amount of activated carbon, and the other steps remained the same.
[0049] Embodiment 5:
[0050] On the basis of Example 2, the finished product was mixed with maleic anhydride in a solvent xylene, the amount of maleic anhydride being 10% of the weight of the finished product, the mixture was heated to 150° C. and maintained for 12 hours to ensure that the modifier and the polyphenylene ether were fully reacted. The reaction was carried out under a nitrogen atmosphere. After the reaction was completed, the product was cooled and washed with an appropriate solvent to remove unreacted modifiers and by-products, and then dried.
[0051] Embodiment 6:
[0052] On the basis of Example 3, the finished product was mixed with maleic anhydride in a solvent xylene, the amount of maleic anhydride being 10% of the weight of the finished product, the mixture was heated to 150° C. and maintained for 12 hours to ensure that the modifier and the polyphenylene ether were fully reacted. The reaction was carried out under a nitrogen atmosphere. After the reaction was completed, the product was cooled and washed with an appropriate solvent to remove unreacted modifiers and by-products, and then dried.
[0053] Embodiment 7:
[0054] On the basis of Example 4, the finished product was mixed with maleic anhydride in a solvent xylene, the amount of maleic anhydride being 10% of the weight of the finished product, the mixture was heated to 150° C. and maintained for 12 hours to ensure that the modifier and the polyphenylene ether were fully reacted. The reaction was carried out under a nitrogen atmosphere. After the reaction was completed, the product was cooled and washed with an appropriate solvent to remove unreacted modifiers and by-products, and then dried.
[0055] See also Figure 2 , parameter description:
[0056] Flexural strength (MPa): shows the maximum bearing capacity of a material under bending load.
[0057] Thermal decomposition temperature (°C): The temperature at which the material begins to decompose, indicating thermal stability.
[0058] Chemical stability score (1-10): Evaluates the material's ability to resist chemical corrosion and reactions.
[0059] Corrosion Resistance Rating (1-10): Rating of a material's ability to resist corrosion.
[0060] Nanoparticle dispersibility score (1-10): evaluates the degree of dispersion of nanoparticles in the polymer matrix.
[0061] Overall performance score (1-100): An overall score that takes into account all of the above factors.
[0062] From Example 1 to Example 7, there is an obvious performance increasing trend, especially in bending strength and thermal decomposition temperature. The addition of copper nanoparticles and graphene (Examples 3 and 4) significantly improves the mechanical properties and thermal stability of the material, and chemical modification (Examples 5, 6, 7) further improves the chemical stability and corrosion resistance.
[0063] This is because the effective surface area of the catalyst can be significantly increased by means of catalyst loading, so that more active sites are exposed to the reactants, resulting in an increase in the reaction rate, because more reactant molecules can simultaneously act with the active sites on the catalyst surface. In addition, loaded catalysts are less likely to agglomerate or sinter than unloaded catalysts. Under high temperature or long-term reaction conditions, unloaded nanoscale catalyst particles are prone to agglomeration, which will lead to a reduction in active surface area and a decrease in catalytic activity. Loading can effectively anchor the catalyst particles, keep them dispersed and stable, thereby extending the service life of the catalyst. Since the catalyst is fixed on a larger carrier, the catalyst can be recovered from the reaction mixture by simple filtration or centrifugation steps without the need for complex liquid phase extraction or washing processes, which not only reduces production costs but also helps protect the environment.
[0064] Secondly, by loading copper nanoparticles and thermally conductive materials (such as carbon nanotubes or graphene) on a high surface area carrier, not only can the dispersion and stability of the catalyst be improved, but also the catalytic efficiency can be improved by enhancing thermal conductivity, thereby achieving a higher reaction rate and better product properties in the synthesis process of polyphenylene ether. Because the influence of temperature in the reaction system is crucial, the addition of thermally conductive materials can make the temperature better distributed and keep the reaction fully proceeding.
[0065] The above are only preferred specific implementations of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for efficiently preparing polyphenylene ether, characterized in that: The following steps are involved: S1, mixing bisphenol A, potassium iodide and sodium hydroxide in a reactor; S2, adding a solvent to the reaction mixture and mixing it thoroughly, adding a catalyst to the mixture, and then heating the reaction; S3. After the reaction is completed, the reaction mixture is cooled to room temperature, and a precipitant is added thereto to precipitate a polyphenylene ether product; S4. The polyphenylene ether product is filtered, washed and dried to obtain a finished product.
2. A method for efficiently preparing polyphenylene ether according to claim 1, characterized in that: In step S1, the molar ratio of bisphenol A to potassium iodide is 1:1.2 to 1:1.8, and the amount of sodium hydroxide used is 15%-25% of the weight of bisphenol A.
3. A method for efficiently preparing polyphenylene ether according to claim 2, characterized in that: In step S2, the solvent is selected from at least one of xylene, dichloromethane and N,N-dimethylformamide, and the amount used is 2 to 5 times the weight of bisphenol A; The catalyst is copper powder, and its usage is 0.1%-0.5% of the weight of bisphenol A.
4. A method for efficiently preparing polyphenylene ether according to claim 3, characterized in that: In step S2, the reaction temperature is controlled between 130° C. and 160° C., and the reaction time is 20 to 60 minutes.
5. A method for efficiently preparing polyphenylene ether according to claim 4, characterized in that: In step S3, the precipitant is selected from at least one of water, ethanol and acetic acid, and the amount of the precipitant added is 30%-50% of the volume of the reaction mixture.
6. The method for efficiently preparing polyphenylene ether according to claim 1, characterized in that: The step S4 modifies the finished product, and the modification treatment includes reacting with at least one modifier selected from maleic anhydride, vinyl triethoxysilane and methyl methacrylate.
7. A method for efficiently preparing polyphenylene ether according to claim 6, characterized in that: The modification process comprises the following steps: S41, mixing the finished product with a modifier in a solvent of toluene or xylene, wherein the amount of the modifier is 1%-10% of the weight of the finished product; S42, heating the mixture to 80° C.-150° C. and maintaining the temperature for 5-12 hours to ensure that the modifier and the polyphenylene ether react fully, and the reaction is carried out under a nitrogen atmosphere; S43. After the reaction is completed, the product is cooled and washed with a suitable solvent to remove unreacted modifier and by-products, and then dried.
8. The method for efficiently preparing polyphenylene ether according to claim 1, characterized in that: The step S2 includes the following steps: S21, select commercially used activated carbon and calcine it at 400°C for 2 hours to remove surface impurities and improve purity, the amount of activated carbon used is 10% of the total reaction system mass; S22, using copper sulfate as a copper source to prepare a 0.1 M solution, and using sodium borohydride (NaBH4) as a reducing agent to ensure complete reduction of copper ions to form copper nanoparticles; S23, ultrasonically treating the mixture for 2 to 4 hours to ensure that the material is evenly dispersed; S24, drying the mixture at 200° C. using a nitrogen atmosphere for 3-5 hours; S25, calcining at 300°C to 500°C for 2 hours, maintained under an inert gas atmosphere.
9. A method for efficiently preparing polyphenylene ether according to claim 8, characterized in that: In the step S22, carbon nanotubes or graphene are added to the solution in an amount of 1% to 5% of the amount of activated carbon.
10. A method for efficiently preparing polyphenylene ether according to any one of claims 1 to 9, characterized in that: The polyphenylene ether product is used for at least one application after filtering, washing and drying, and the application includes electronic materials, automobile parts or medical devices.
Citation Information
Patent Citations
Low-molecular-weight polyphenyl ether and preparation method thereof
CN118420897A
Catalysts for oxidative coupling of phenols
US4438284A